1980
DOI: 10.1159/000115130
|View full text |Cite
|
Sign up to set email alerts
|

Plasma High-Density Lipoprotein Cholesterol in Epileptics Treated with Various Anticonvulsants

Abstract: Plasma high-density lipoprotein (HDL) cholesterol in 97 epileptics on long-term anticonvulsant therapy was investigated. Therapy with phenytoin alone or in combination with carbamazepine or phenobarbital was associated with elevated plasma HDL cholesterol levels as compared with controls. HDL cholesterol in patients treated with carbamazepine did not diverge from control values. Patients treated with phenytoin and phenobarbital in combination showed higher HDL cholesterol levels than those treated with phenyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…Our results agree with those of most authors finding increased HDL cholesterol levels in patients receiving AEDs (14)(15)(16)(17)(18)(19)(20)(21)(22), with the exception of carbamazepine monotherapy, as reported by Luoma et al (14).…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with those of most authors finding increased HDL cholesterol levels in patients receiving AEDs (14)(15)(16)(17)(18)(19)(20)(21)(22), with the exception of carbamazepine monotherapy, as reported by Luoma et al (14).…”
Section: Discussionsupporting
confidence: 93%
“…The observed increase in HDL-c in patients treated with both nevirapine and EFV has been shown to be accompanied by an increase in levels of apo A1 in plasma. 11,27 Favorable dose-dependent increases in levels of HDL-c [28][29][30] and apo A1 31 have also been observed in patients receiving antiepileptic agents. One study suggests that the observed increase in apo A1 mRNA expression in cell lines exposed to phenobarbital is a result of an increase in apo A1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…14,16 Equally, our results do not support the HDL-C = high-density lipoprotein cholesterol; LDL-C = low-density lipoprotein cholesterol; VLDL-C = very-low-density lipoprotein cholesterol. 5,7,13,15,18 Reports on the effects of valproic acid on lipid measurements are conflicting. Statistically significant difference with respect to corresponding treatment mean (normal diet): ***P < .05.…”
Section: Discussionmentioning
confidence: 99%